Components of defence strategies in society’s information environment: a case study based on the grounded theory - Mustonen-Ollila Erja Birgitta; Lehto Martti; Heikkonen Jukka (War Studies University, 2025)
The goal of this study is to explore the components of defence strategies faced by society in its information environment, and how these strategies are inter-related. This qualitative in-depth case study applied past research and empirical evidence to identify the components of defence strategies in a society’s information environment. The data collected was analysed using the Grounded Theory approach and a conceptual framework with the components of defence strategies and the relationships between these components was developed using the Grounded Theory. This study shows that the goal of politically and militarily hostile actors is to weaken society’s information environment, and that their operations are coordinated and carried out over a long time period. The data validates past studies and reveals relationships between the components of defence strategies. These relationships increase confidence in the validity of these components and their relationships, and expand the emerging theory. First, the data and findings showed 16 inter-connected components of defence strategies. Second, they showed that the political, military, societal, power, and personal goals of the hostile actors carrying out cyber operations and cyber attacks are to weaken society’s information environment. Third, they revealed that cyber operations and cyber attacks against networks, information and infrastructures are coordinated operations, carried out over a long time period. Finally, it was revealed that the actors defending society’s information environment must rapidly change their own components of defence strategies and use the newest tools and methods for these components in networks, infrastructures and social media.